2013
DOI: 10.3389/fneur.2013.00067
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s Disease Rigidity: Relation to Brain Connectivity and Motor Performance

Abstract: Objective: (1) To determine the brain connectivity pattern associated with clinical rigidity scores in Parkinson’s disease (PD) and (2) to determine the relation between clinically assessed rigidity and quantitative metrics of motor performance.Background: Rigidity, the resistance to passive movement, is exacerbated in PD by asking the subject to move the contralateral limb, implying that rigidity involves a distributed brain network. Rigidity mainly affects subjects when they attempt to move; yet the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 50 publications
2
35
0
1
Order By: Relevance
“…Furthermore, a later study has revealed that severity of rigidity correlated with functional connectivity between the cerebellum, the motor, temporal and occipital cortices, and the nucleus caudatus in mild-moderate PD patients OFF medication, while they were performing a motor task involving external and internal (memory) cues (Baradaran et al, 2013). To sum up, these findings suggested that rigidity is not only associated with STN firing frequency, but also with altered functioning of a widespread brain network.…”
Section: Neural Substratesmentioning
confidence: 92%
“…Furthermore, a later study has revealed that severity of rigidity correlated with functional connectivity between the cerebellum, the motor, temporal and occipital cortices, and the nucleus caudatus in mild-moderate PD patients OFF medication, while they were performing a motor task involving external and internal (memory) cues (Baradaran et al, 2013). To sum up, these findings suggested that rigidity is not only associated with STN firing frequency, but also with altered functioning of a widespread brain network.…”
Section: Neural Substratesmentioning
confidence: 92%
“…33 Additionally, freezing of gait and balance confidence were assessed using the Freezing of Gait questionnaire 34 and the Activities-specific Balance Confidence scale, 35,36 respectively. Postural instability and gait disability (PIGD) were assessed by summing the scores for Items 13 to 15 and 27 to 30 from the UPDRS, 37 while PD subtypes 38 and a global rigidity score 39 were determined from the UPDRS using previously described methods. All assessments were completed within 1 to 2 hours of patients receiving their usual anti-parkinsonian treatment to ensure that they were optimally medicated.…”
Section: Clinical Assessmentmentioning
confidence: 99%
“…Kaut et al 16 comprovaram que a PV possibilitou a melhora da rigidez muscular e consequentemente a melhora da marcha para execução das AVD. Baradaran et al 22 enfatizam que a rigidez está relacionada à limitação funcional em pacientes com DP. A vibração favorece a redução da rigidez devido à ativação do reflexo miotático, por meio da excitação dos neurônios motores α, possibilitando um aumento das informações proprioceptivas, provenientes do estimulo gerado pela PV.…”
Section: Discussionunclassified